Enhancing the performance of Packet Retrieval mechanism in wireless communication by suing an Orthogonal Clustered searching Algorithm (OCSA) - an Overview - Sirajudeen, M Mohamed; Siddiq, M .Abubacker (IJRDO -Journal of Computer Science Engineering, 2015)
In general either it may be a wired communication or wireless communication, the message /packet retrieval for the appropriate communication play an important role in order to determine the performance. There are two main functions performed by a routing algorithm are the selection of routes for various origin-destination pairs and the delivery of messages to their correct destination once the routes are selected. The second function is conceptually straightforward using a variety of protocols and data structures in order to involve in the packet retrieval operation. This paper mainly focusing on to reduce the time delay of the retrieval mechanisms of packet from the appropriate routers and improve the performance of the communication by using the proposed Orthogonal Clustered searching Algorithm (OCSA).